Lay health worker-delivered and technology-based interventions for sexual and reproductive health among adolescents and young adults in low- and middle-income countries: protocol for a scoping review - Kern, Matthias; Neumann, Christine; Bosompim, Benjamin; Ann, Dorit; Kurniawan, Adi Lukas; Dlamini, Nolwazi; Nabukeera, Sarah; Machanyangwa, Sphindile; Tewahido, Dagmawit; Shinde, Sachin; Bukenya, Justine (BMJ open, 2025)
Background Adolescents and young adults (AYAs) in low- and middle-income countries (LMICs) are at high risk of harmful sexual and reproductive health (SRH) practices due to limited knowledge, low availability or acceptability of modern contraceptives, gender inequality and cultural practices like child marriage. Preventive and educational interventions by lay health workers or through technological means are a cost-effective and scalable solution. Unfortunately, too little is currently known about the scope, content and conditions of the effectiveness and sustainability of these approaches and synthetic evidence on this topic is scarce. To help fill this knowledge gap and to identify where further research is needed, we will conduct a scoping review of technology-based or lay health-worker delivered preventive and educational SRH interventions targeting AYAs in LMICs. This information is valuable to both policymakers and researchers as it provides a synthesis of existing interventions, highlights best practices for their implementation and identifies potential avenues for future research. - Methods This review will include studies on SRH preventive and educational interventions targeting AYAs aged 10-24 years in LMICs. It encompasses interventions delivered by lay health workers or via technological means, assessing various outcomes including but not limited to SRH literacy, sexual risk behaviours, pregnancies, sexually transmitted infections and gender-based violence. Key databases, including PubMed via MEDLINE and Embase, will be searched from 1 January 2000 up to 23 January 2024, using a comprehensive search strategy. Screening will be conducted using Covidence software. Data extraction will cover study details, methods, intervention strategies, outcomes and findings. A narrative synthesis will be conducted following synthesis without meta-analysis guidelines. - Ethics and dissemination The scope of this scoping review is limited to publicly accessible databases that do not require prior ethical approval for access. The findings will be disseminated through peer-reviewed journal publications, as well as presentations at national and international conferences and stakeholder meetings in LMICs. - Scoping review registration The final protocol is prospectively registered with the Open Science Framework on 7 May 2024 (osf.io/vna2z).